2014
DOI: 10.1128/jvi.03018-13
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient Type I Interferon-Mediated Antiviral Protection of Primary Mouse Neurons Is Associated with the Lack of Apolipoprotein L9 Expression

Abstract: We examined the antiviral response promoted by type I interferons (IFN) in primary mouse neurons. IFN treatment of neuron cultures strongly upregulated the transcription of IFN-stimulated genes but conferred a surprisingly low resistance to infection by neurotropic viruses such as Theiler's murine encephalomyelitis virus (TMEV) or vesicular stomatitis virus (VSV). Response of primary mouse neurons to IFN treatment was heterogeneous, as many neurons failed to express the typical IFN response marker Mx1 after IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Interestingly, increased expression of ApoLs has been observed in cervical and breast cancer (Ahn et al, 2004; Jung et al, 2005). Apol9b has been implicated in anti-viral protection in L929 cells and primary neurons, but the extent and mechanism of such protection was unclear (Kreit et al, 2014). In this report, we show that Apol9a can be secreted and promotes epithelial proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased expression of ApoLs has been observed in cervical and breast cancer (Ahn et al, 2004; Jung et al, 2005). Apol9b has been implicated in anti-viral protection in L929 cells and primary neurons, but the extent and mechanism of such protection was unclear (Kreit et al, 2014). In this report, we show that Apol9a can be secreted and promotes epithelial proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably neurons, like germ cells, are permissive to retrotransposition (Upton et al 2015) and relatively nonresponsive to type I interferons (Lin et al 2013;Kreit et al 2014). Transcripts of the murine PIWI-clade partner of most pachytene piRNAs (MIWI) can be detected in a distribution overlapping highly BDV-susceptible cells in the cerebellum, dentate gyrus, and olfactory bulb (Lein et al 2007;Ackermann et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been no studies that resolved whether an innate immune response mounted within the brain parenchyma can limit viral spread, especially along neuronal circuitry. Studies using in vitro-cultured neurons have attempted to address whether an innate immune response can restrict virus spread among neurons but produced conflicting results, including for VSV (57,58). These previous studies raised the issue of whether virus spread among neurons in the immunologically distinct parenchyma can be limited by the innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that viral infection can stimulate expression of ISGs and proinflammatory cytokines in cultured CNS cells and in the brain (8,10,55,56) and that both neurons and glia are responsive to IFN treatment (57)(58)(59). Additionally, studies tracking virus spread into the brain from peripheral sites of inoculation have highlighted the importance of the innate immune response in preventing high virus load within the brain (14,50,60,61).…”
Section: Discussionmentioning
confidence: 99%